2004
DOI: 10.1520/jai12352
|View full text |Cite
|
Sign up to set email alerts
|

Role of Iron for Hydrogen Absorption Mechanism in Zirconium Alloys

Abstract: The latest PIE results of Zry-2 and HiFi alloy (0.4 %Fe-Zry2) showed that iron addition reduces the hydrogen pick-up ratio. In order to clarify this lower hydrogen absorption mechanism, three types of experiments were carried out for both alloys: (1) Measurements of the hydrogen pick-up ratio in the pre-transition region using an autoclave. (2) CPD (Contact Potential Difference) and FBP (Flat-band Potential) measurements of oxide film using a High Temperature Kelvin system and Pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We also found that the hydrogen diffusivity in the barrier layer increased when the hydrogen pickup fraction increased near the kinetic transition in the oxide layer of the Zry-2 type alloy [19]. The relationship between the barrierness of the oxide layers and the hydrogen diffusivity has been also pointed out in some studies [20][21][22][23], so this kind of hydrogen diffusion measurements on Zr-2.5Nb will discover the relationship between the barrierness to oxidation and that to hydrogen pickup.…”
Section: Discussionmentioning
confidence: 71%
“…We also found that the hydrogen diffusivity in the barrier layer increased when the hydrogen pickup fraction increased near the kinetic transition in the oxide layer of the Zry-2 type alloy [19]. The relationship between the barrierness of the oxide layers and the hydrogen diffusivity has been also pointed out in some studies [20][21][22][23], so this kind of hydrogen diffusion measurements on Zr-2.5Nb will discover the relationship between the barrierness to oxidation and that to hydrogen pickup.…”
Section: Discussionmentioning
confidence: 71%
“…According to some papers [2], the precipitate in the oxide film plays an important role as the window of hydrogen absorption. Corrosion test results [7] of intermetallic compounds indicate that, in the role of window of hydrogen absorption, the contribution of Zr(Fe,Cr) 2 seems to be greater than that of Zr 2 (Fe,Ni), because the corrosion rate of Zr(Fe,Cr) 2 is smaller than that of Zr 2 (Fe,Ni), so that Zr(Fe,Cr) 2 possibly survives longer than Zr 2 (Fe,Ni). Based on this result, the hydrogen absorption property of zirconium alloy appears to be controlled by the hydrogen permeability of the precipitate.…”
Section: ) Hydrogen Absorption Mechanismmentioning
confidence: 99%
“…In addition, the corrosion resistance of Nb-containing zirconium alloys is closely related to the heat treatment process. Studies have shown [10][11] that β quenching make stable elements Nb, Fe, and Cr supersaturate in the βZr, which improved the nodular corrosion performance, inversely, made the uniform corrosion rate get faster [12][13]. The intermediate annealing temperature during the cold processing of Nb-containing zirconium alloys should not exceed a certain temperature, otherwise β-Zr would form, which was unfavorable to corrosion.…”
Section: Introductionmentioning
confidence: 99%